(untitled) (Research, Society and Development, 2024)
This article’s main focus is the investigation into over-indebtedness in Brazil due to the COVID-19 pandemic. The methodology used to carry out this study is a qualitative documentary and reflective study, which generated a substantial impact on the economy not only in Brazil, but in the World, directly impacting the financial situation of individuals. In Brazilian territory, this repercussion was manifested through a significant increase in consumer debt, a direct result of the economic difficulties imposed by the pandemic scenario and leading consumers to default on financial institutions. Consumer over-indebtedness is a social and economic phenomenon that occurs when an individual, acting in good faith, accumulates debts to such an extent that they become unable to pay them within their economic capacity, without compromising their existential minimum. This concept covers not only present debts, but also future ones, excluding, however, those contracted with the tax authorities. Over-indebtedness is a problem that affects not only consumers and their families, but also the economy as a whole, as it reduces consumption capacity and can lead to exclusion from the credit market, being a complex challenge that requires a multidisciplinary approach, involving education, legislation and public policies focused on consumer protection and the promotion of more responsible credit.